Life lessons: examining sources of racial and ethnic disparity in federal life without parole sentences - Johnson, Brian (Criminology, 2021)
Alongside capital punishment, sentences to life withoutthe possibility of parole are one of the most distinctiveaspects of the American system of criminal punishment.Unlike the death penalty, though, almost no empiricalwork hasexaminedthedecisionto impose lifeimprison-ment. The current study analyzes several years of recentfederal sentencing data (FY2010–FY2017) to investigateunderlying sources of racial disparity in life withoutparole sentences. The analysis reveals disparities in whoreceives life imprisonment, but it finds these differencesareattributablemostlytoindirectmechanismsbuiltintothe federal sentencing system, such as the mode of con-viction, mandatory minimums, and guidelines depar-tures. Both Black and Hispanic offenders are more likelyto be eligible for life sentences under the federal guide-lines,butconditionalonbeingeligible,theyarenotmorelikely to receive life sentences. Findings are discussed inrelationtoongoingdebatesoverracialinequalityandthegrowing role that life imprisonment plays in Americanexceptionalism in punishment.